Z zagadnień struktury organów administracji rolnej i prawnych form ich działania: [The problems of the structure of agrarian administration bodies and the legal forms of their functioning] (Studia Prawnicze / The Legal Studies, 1964)
Considering the wide range of activities of the agrarian administration bodies in the Polish People’s Republic, we clearly see a dialectical connection between the content of the tasks assigned to them and their organization as well as forms of functioning.Generally speaking, the bodies for the implementation of agrarian reform created in the first years of the Polish People’s Republic did not fit into the framework of schemes and ideas of professional and special state bodies not only and not mainly due to the great involvement of the public element in them (the only public element of clearly defined class profile appeared in some of them) but primarily due to the fact that some of them were subsidiary bodies and deprived of the right to finally solve the problems, so they could not resort to coercive measures in their actions. According to the theory of law, a state administration body should meet the following criteria: a) acting on behalf of the state, b) organizational disintegration, c) competence established by law, d) personal substratum of the body, e) appropriate forms of functioning.Just a few bodies involved in the implementation of the agrarian reform met only certain criteria, for example: acting on behalf of the state based on the law, the competence established by law and the administrative activity.In addition, in 1944-1950, it was not yet possible to observe the fundamental feature of administrative bodies in our state regarding the local agrarian bodies, namely: subordination — direct or indirect — to representative bodies with full power. This principle applied only to the highest representative body. During that period, the people’s councils carried out their local supreme management only through planning the public activities and supervising the administration, while methods and forms of planning and supervising were only being developed at that time. According to the law of 1958 on people’s councils, the departments of these councils were endowed with the appropriate competence as special administrative bodies in the narrow sense and received independence in functioning.In case of agrarian issues, such bodies are the agricultural and silvicultural departments of powiat (county) and voivodeship people’s councils which are usually called agrarian bodies in the latest regulations. Their competence in this area is currently limited mainly to the following points: a) the removal of a strictly defined, narrow range of issues on which decisions are made by county commissions; b) the removal of a limited range of issues (although not as strictly defined as in the previous case) subject to the collegial decisions of the presidiums of people’s councils, and c) the removal of issues that are under the jurisdiction of the presidiums and executive bureaus of the community (communal) people’s councils.The form of functioning of the agrarian bodies using the administrative acts has always been of great importance in the activities related to the restructuring the agrarian system; sometimes it has been the main form, sometimes it has been only the auxiliary form. However, it would not be possible to carry out agrarian reform in the Polish People’s Republic without resorting to the form of functioning by means of the administrative acts.